Doing Participatory Action Research in a Multicase Study: A Methodological Example. Issue 5 (10th December 2015) - Fletcher, Amber J.; MacPhee, Maura; Dickson, Graham
In this article, we describe an approach for conducting participatory action research (PAR) in a longitudinal multicase study, with particular focus on cross-case analysis. Existing literature has documented the practice of PAR in single-case studies, but far less has been written on how to conduct PAR across multiple cases. There is also a need for instructional examples of multicase study application, particularly methods of cross-case analysis. In PAR, research methods—including data analysis methods—have the power to shape participant inclusion or exclusion, involvement or attrition, and mobilization of knowledge in real time. In response to these challenges, we discuss the analysis methods used in a PAR study of health leadership in Canada. The project, which consisted of six case studies of leadership in major health system change, involved health leaders as collaborators. We address the challenges of doing PAR with collaborators facing time limitations and suggest a project structure for involving collaborators at critical junctures. We present a detailed, two-part method for conducting cross-case data analysis. Our method involved targeted collaborator involvement in data interpretation while also ensuring faithfulness to the coded data. We describe our process for mobilizing study findings through a deliberative dialogue with health leaders.